1999
DOI: 10.1006/dbio.1999.9373
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Matrix Metalloproteinase 2 (MMP-2) in Ectomesenchyme-Derived Tissues of the Patch Mutant Mouse: Regulation of MMP-2 by PDGF and Effects on Mesenchymal Cell Migration

Abstract: Platelet-derived growth factors (PDGF) regulate cell proliferation, survival, morphology, and migration, as well as deposition and turnover of the extracellular matrix. Important roles for the A form of PDGF (PDGF-A) during connective tissue morphogenesis have been highlighted by the murine Patch mutation, which includes a deletion of the alpha subunit of the PDGF receptor. Homozygous (Ph/Ph) embryos exhibit multiple connective tissue defects including cleft face (involving the first branchial arch and fronton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 34 publications
1
69
0
Order By: Relevance
“…Ablation of the PDGF-receptor α-subunit enhances the formation and migration of mesenchymal-like cells, and decreases MMP2 activity (62). VEGF is understood to be associated with PDGF and induces angiogenesis, which also causes EMT (63).…”
Section: Discussionmentioning
confidence: 99%
“…Ablation of the PDGF-receptor α-subunit enhances the formation and migration of mesenchymal-like cells, and decreases MMP2 activity (62). VEGF is understood to be associated with PDGF and induces angiogenesis, which also causes EMT (63).…”
Section: Discussionmentioning
confidence: 99%
“…Direct inhibition of MMPs in mouse neural crest cultures (Robbins et al, 1999) or in chick neural crest cultures (Cai and Brauer, 2002) further show that this class of matrix-degrading enzymes may stimulate motility. Moreover, in the mouse mutant Patch, in which craniofacial mesenchyme does not disperse properly, MMP-2 activity is depressed (Robbins et al, 1999). Of interest, our cell culture studies and embryo studies suggest that once neural crest cells are fully mesenchymal, they are not affected by loss of MMP-2 activity.…”
Section: Proteases and Cell Motilitymentioning
confidence: 93%
“…Previous studies also showed that MMP-2 is expressed in migrating chick endocardial cushion cells (Alexander et al, 1997;Cai et al, 2000). MMP-2 is expressed in the mesenchyme of the mouse embryo Robbins et al, 1999), although the cranial neural crest was the only MMP-2-expressing cell population in those studies that overlapped with chicken MMP-2 expression. Direct inhibition of MMPs in mouse neural crest cultures (Robbins et al, 1999) or in chick neural crest cultures (Cai and Brauer, 2002) further show that this class of matrix-degrading enzymes may stimulate motility.…”
Section: Proteases and Cell Motilitymentioning
confidence: 94%
See 1 more Smart Citation
“…S3). [26][27][28][29] In this work, we have further demonstrated that hydrodynamics might influence ESC differentiation through temporal modulation of ECM and GF gene and protein expression. Although our results illustrate similar kinetic profiles between static and rotary culture systems for many of the specific genes examined, the rotary environment elicited increases in expression of a larger subset of genes throughout the time course of EB analysis.…”
Section: Fig 4 Different Classes Of Extracellular Matrix (Ecm) (A-hmentioning
confidence: 94%